Investigating the Effect of In Ovo Injection of Silver Nanoparticles on Fat Uptake and Development in Broiler and Layer Hatchlings - Lane Pineda; André Chwalibog; Ewa Sawosz; Anna Hotowy; Jan Elnif; Filip Sawosz (Journal of Nanotechnology)
Silver nanoparticles (AgNano) as carrier of available oxygen (O2) and with high surface reactivity may increase O2 consumption, enhance fat uptake (FU), and stimulate growth and development. The objective was to investigate the effects of in ovo injection of AgNano on the metabolic rate (O2 consumption, CO2 production, and heat production, HP), fat uptake, and the development of broiler and layer hatchlings. AgNano concentrations (50, 75, and 100 mg/kg) were injected in ovo at day 1 of incubation to different breeds of broiler and layer chicken embryos. Oxygen consumption and subsequently FU did not increase linearly following AgNano treatment. FU was lower in hatchlings treated with 50 and 100 mg AgNano/kg, but surprisingly not in hatchlings treated with 75 mg AgNano/kg. Interestingly, the difference in FU between treatments was not reflected in hatchling development. The results indicated that AgNano affected metabolic rate and FU; however, it did not influence the development of hatchlings. This suggests that in ovo injection of AgNano reduces the need to use yolk fat as an energy source during embryonic development and consequently the remaining fat in the residual yolk sac may provide a potent source of nutritional reserves for chicks of few days after hatching.